2014
DOI: 10.1038/cddis.2014.76
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic action by multi-targeting compounds produces a potent compound combination for human NSCLC both in vitro and in vivo

Abstract: By screening a collection of one hundred combinations of thiazolidinone compounds, we identified one combination (M4) that synergistically inhibited the growth of H460 and H460/TaxR cells and tumor growth in H460/TaxR xenograft mice. A whole genome microarray assay showed that genes involved in negative regulation of microtubule polymerization or depolymerization, intracellular protein kinase cascade, positive regulation of histone acetylation, cell cycle arrest and apoptosis were upregulated. Further analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…To explore the possible targets of TBPT, we determined the global gene expression profile of H460 TaxR cells after TBPT treatment using an Agilent whole-human genome oligo microarray platform. 20 The microarray analysis revealed that 534 genes were suppressed and 410 genes were upregulated (≥2-fold) in H460 TaxR cells following TBPT treatment (2 μ M, 4 h). The gene ontology analysis indicated that genes involved in regulating microtubule cytoskeleton and nucleus functions were altered by TBPT ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…To explore the possible targets of TBPT, we determined the global gene expression profile of H460 TaxR cells after TBPT treatment using an Agilent whole-human genome oligo microarray platform. 20 The microarray analysis revealed that 534 genes were suppressed and 410 genes were upregulated (≥2-fold) in H460 TaxR cells following TBPT treatment (2 μ M, 4 h). The gene ontology analysis indicated that genes involved in regulating microtubule cytoskeleton and nucleus functions were altered by TBPT ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 97%
“…15 , 16 , 17 In an effort to redeploy anti-depressant compound scaffold for anticancer applications, we synthesized a series of 27 novel tricyclic thiazepine derivatives 18 and screened these compounds against the NSCLC cell line H460 and its drug-resistant variant H460 TaxR (manuscript submitted). 19 , 20 , 21 The drug-resistant H460 TaxR cell line was obtained by treating H460 cells initially with 5 nM PTX and increased doses up to 100 nM, leading to a remarkable overexpression of P-gp (245-folds, Figure 1b ) among other possible alterations. Compared with H460, H460 TaxR is highly resistant to many clinical drugs, including PTX, vincristine and doxorubicin, because of the drug pump P-gp ( Figure 1c , Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were treated with the drug combination and analyzed using a CellTiter-Blue assay (Promega) according to the manufacturer's instructions. Drug synergy was determined by the isobologram and combination-index methods using CalcuSyn software 2.1 (Biosoft) 59 . Detailed methods are described in the Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%